math

how to you find a composite function form of y in this problem?

y = 1/[(x^2+3x-5)^3]


I don't understand your question. Composite functions require two functions. You listed one. Please amplify.


That's what I thought at first. But I am thinking I might need to substitute y in place of x and x in place of y?

  1. πŸ‘ 0
  2. πŸ‘Ž 0
  3. πŸ‘ 38
asked by greg

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math22

    1. Write the composite function in the form f(g(x)). [Identify the inner function u = g(x) and the outer function y = f(u).] y= (g(x), f(u)) = 2. Write the composite function in the form f(g(x)). [Identify the inner function u =

    asked by Anonymous on October 7, 2014
  2. CAL

    Hi, im lost in theses three problems. Please help. Thank you so much!!! 1. Write the composite function in the form f(g(x)). [Identify the inner function u = g(x) and the outer function y = f(u).] y = 3 squareroot all 1 + 5x

    asked by Anonymous on October 7, 2014
  3. Calculus. I need help!

    Write the composite function in the form f(g(x)). [Identify the inner function u=g(x) and the outer function y=f(u).] Then find the derivative dy/dx. y=√sinx √ is square root.

    asked by danny on February 25, 2012
  4. functions

    For each problem, construct two composite functions, . Evaluate each composite function for x=2 ok i have not dealt with composite functions can I please get some help with this as I have 20 questions to do can someone show me

    asked by Johnathan on October 18, 2013
  5. algebra functions

    can someone please check my answer For each problem, construct two composite functions, . Evaluate each composite function for x=2 f(x)=3x g(x)=1/x f(g)*(x)=3x(1)/x x=2 3x(1)/x=6 g(f)*(x)=(3x)=2*3x=6 x=2 3*(2)=6*6=36

    asked by tani on October 17, 2013
  6. algebra functions check my answer

    For each problem, construct two composite functions, . Evaluate each composite function for x=2 f(x)=3x g(x)=1/x f(g)*(x)=3x(1)/x x=2 3x(1)/x=6 g(f)*(x)=(3x)=2*3x=6 x=2 3*(2)=6*6=36

    asked by tani on October 17, 2013
  7. math

    how would this equation look: y=f(x+3) when y=f(x)= x^2 would it look like so.... x^2(x+3) adam, there's a slight problem with your notation in the expression y = f(x+3). Ordinarily we wouldn't put an expression in place of a

    asked by adam on July 6, 2006
  8. calculus

    Suppose that f(x)= square root of x and g(x)= 3x-4 and you are asked to evaluvate the composite function f(g(0)). What is the complication that occurs in trying to find that composite function value? For waht values of x is it

    asked by Pauline on February 3, 2011
  9. maths

    (a)(i)use the composite rule to differentiate the function f(x)=(x^2-6x+23)^(3/2). (ii)use the composite rule and your answer to part (a)(i) to show that the function g(x)=(x-2)/(x^2-6x+23)^(3/2) has derivative

    asked by alan on May 20, 2011
  10. college algebra

    Let f(x) = square root (x + 2) and g(x) = x^2 βˆ’ 2. Determine the domain of the composite function. (Enter your answer using interval notation.) f compose f ______? & Find the composite function. (f compose f)(x) = _____?

    asked by Dee on October 21, 2013

More Similar Questions